QR Code Increases Knowledge The Dangers of Free Sex - Elvi Destariyani; Yuniarti Yuniarti (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
In Bengkulu Province, 1.0% of teenagers have engaged in premarital sexual activity with their partners, with a prevalence of 1.6% among male teenagers and 0.6% among female teenagers. This study aims to examine the effectiveness of QR Code digital media in enhancing teenagers' awareness of the risks associated with casual sex at State Senior High School 8 Bengkulu. The research adopts a quasi-experimental design using a pre-test and post-test with a control group methodology. The sampling technique employed proportionate stratified random sampling, selecting a total of 72 students 36 in the intervention group and 36 in the control group. The analysis was conducted using the Wilcoxon test and the Mann-Whitney test. The findings indicate that QR Code digital media (p = 0.000) and Instagram (p = 0.000) were both effective in increasing adolescents' knowledge regarding the risks of casual sex. The mean difference in knowledge levels was 5.69 for QR Code digital media and 5.41 for Instagram. Furthermore, QR Code digital media demonstrated a greater impact (0.47) in improving teenagers' awareness of these risks at State Senior High School 08 and State Senior High School 10, Bengkulu. These findings highlight the potential of QR Code digital media as an effective educational tool. It is recommended that academics, educational institutions, and researchers further integrate and develop digital media-based learning strategies to enhance teenagers' knowledge, particularly regarding sexual health education. Keywords: Teenagers; Dangers of free sex; QR Code; Instagram; Knowledge